Evaluation of six commercial point-of-care tests for diagnosis of acute dengue infections: The need for combining NS1 antigen and IgM/IgG antibody detection to achieve acceptable levels of accuracy - Stuart D. Blacksell (2018)
Six assays were evaluated in this study to determine their suitability for the diagnosis of acute dengue infection using samples from 259 Sri Lankan patients with acute fevers (99 confirmed dengue cases and 160 patients with other confirmed acute febrile illnesses): (i) the Merlin dengue fever IgG & IgM combo device (Merlin), (ii) the Standard Diagnostics Dengue Duo nonstructural 1 (NS1) antigen and IgG/IgM combo device (Standard Diagnostics, South Korea), (iii) the Biosynex Immunoquick dengue fever IgG and IgM (Biosynex, France) assay, (iv) the Bio-Rad NS1 antigen strip (Bio-Rad, France), (v) the Panbio Dengue Duo IgG/IgM Cassette (Inverness, Australia), and (vi) the Panbio dengue NS1 antigen strip (Inverness, Australia). The median number of days of fever prior to admission sample collection was 5 days (interquartile range, 3 to 7 days). Sensitivity and specificity of the NS1 antigen tests ranged from 49 to 59% and from 93 to 99%, respectively, and sensitivity and sensitivity of the IgM antibody test ranged from 71 to 80% and from 46 to 90%, respectively. Combining the NS1 antigen and IgM antibody results from the Standard Diagnostics Dengue Duo test gave the best compromise of sensitivity and specificity (93% and 89%, respectively) and provided the best sensitivity in patients presenting at different times after fever onset. The Merlin IgM/IgG antibody tests correctly classified 64% and 86% of the primary and secondary dengue infection cases, respectively, and the Standard Diagnostics IgM/IgG antibody tests correctly classified 71% and 83% of the primary and secondary dengue infection cases, respectively. This study provides strong evidence of the value of combining dengue antigen- and antibody-based test results in the rapid diagnostic test (RDT) format for the acute diagnosis of dengue. Copyright © 2011, American Society for Microbiology. All Rights Reserved.